Depression in the Primary Caregivers of Patients with Substance use Disorder - Farasat Ali, Wasif Baig, Muhammad Saad, Saima Tabassum, Muhammad Sohail Aslam, Farheen Zahra, Adeel Khalid Choudhary (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Caregiving to substance-use disorder patients had a significant impact on mental and physical health which needs some modalities to be developed to support the caregiver’s self-care. Objectives: To determine the frequency of depression among caregivers of patients with Substance use disorder Setting: Department of psychiatry, Ganga Ram Hospital, Lahore Material and Methods: Total 100 caregivers of either gender of age 20 to 50 years old, of patients with substance use disorder. All those with significant physical, surgical, or psychiatric illness and/or mental retardation, dependence of more than one drug simultaneously, intravenous drug users, history of any past psychiatric illness in caregivers, care givers with medical problems (Diabetes, Hypertension, Asthma and COPD) that may mask depressive symptoms were excluded. For Substance use disorder DSM5 criterion was applied to the patient. Conclusion: We concluded that frequency of depression is higher among caregivers of patients with Substance use disorder which needs early intervention to reduce their mental health.